2019
DOI: 10.5812/archcid.83263
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Biofilm Activity of Curcumin Nanoparticles in Acinetobacter baumannii: A Culture-Based and Molecular Approach

Abstract: Background: Acinetobacter baumannii is one of the most important opportunistic and biofilms-forming microorganisms. Its biofilm structure provides an effective barrier against the antimicrobial penetration and increases the drug resistance of Acinetobacter baumannii by 1000× compared with plankton cells. However, nanoparticles have recently reported as suitable tools to prevent biofilm formation. Objectives: The aim of this study was to investigate the effect of curcumin nanoparticles on biofilm gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…When Csu is inactivated , the ability of pili production and subsequently the ability of bacteria to format biofilms is inhibited 80 . Finally, we concluded that decreasing the expression of bap, OmpA, and csuA/B by AgNPs is a main approach for decreasing biofilm activity of A. baumannii that will help in reducing antibiotic resistance mechanisms 81 . The limitations of our study included lack of an in vivo study, which we plan to study in the future work.…”
Section: Discussionmentioning
confidence: 86%
“…When Csu is inactivated , the ability of pili production and subsequently the ability of bacteria to format biofilms is inhibited 80 . Finally, we concluded that decreasing the expression of bap, OmpA, and csuA/B by AgNPs is a main approach for decreasing biofilm activity of A. baumannii that will help in reducing antibiotic resistance mechanisms 81 . The limitations of our study included lack of an in vivo study, which we plan to study in the future work.…”
Section: Discussionmentioning
confidence: 86%
“…The mechanism by which the process occurs is due to its ability to induce ROS. Curcumin demonstrated better antibiofilm activity than the drug nisidine and had an effect compared to that of chloramphenicol [116], with a proven antibiofilm effect on A. baumannii following in vitro tests [67,117]. A. baumannii is one of the most common microorganisms found in nosocomial and chronic infections, with a high resistance to antimicrobials and antibiotics [115][116][117][118].…”
Section: Methods Of Obtaining and Antiviral Antifungal And Antibacter...mentioning
confidence: 99%
“…Curcumin is known in traditional medicine, especially in India, for use in treating fever, skin infections, and to facilitate digestion due to its anti-inflammatory [6][7][8], antiviral , and antibacterial [63,117] properties. In the last two years, because of the COVID-19 pandemic, the congestion of hospitals has led to an increased level of nosocomial infections [136][137][138][139].…”
Section: Additive For Health Care Productsmentioning
confidence: 99%
“…The interaction between negatively charged eDNA and positively charged AgNPs is an important factor in the inhibition of biofilms [184,185]. Additionally, selenium, curcumin, and aluminum oxide NPs were all found to inhibit the growth of A. baumannii biofilms [186][187][188].…”
Section: Nanoparticles (Nps)mentioning
confidence: 99%